Peri-procedural and mid-term follow-up age-related differences in leadless pacemaker implantation: Insights from a multicenter European registry. (15th January 2023) - Gulletta, Simone; Schiavone, Marco; Gasperetti, Alessio; Breitenstein, Alexander; Palmisano, Pietro; Mitacchione, Gianfranco; Chierchia, Gian Battista; Montemerlo, Elisabetta; Statuto, Giovanni; Russo, Giulia; Casella, Michela; Vitali, Francesco; et al.
Abstract: Background: Age-related differences on leadless pacemaker (LP) are poorly described. Aim of this study was to compare clinical indications, periprocedural and mid-term device-associated outcomes in a large real-world cohort of LP patients, stratified by age at implantation. Methods: Two cohorts of younger and older patients (≤50 and > 50 years old) were retrieved from the iLEAPER registry. The primary outcome was to compare the underlying indication why a LP was preferred over a transvenous PM across the two cohorts. Rates of peri-procedural and mid-term follow-up major complications as well as LP electrical performance were deemed secondary outcomes. Results: 1154 patients were enrolled, with younger patients representing 6.2% of the entire cohort. Infective and vascular concerns were the most frequent characteristics that led to a LP implantation in the older cohort (45.8% vs 67.7%, p  < 0.001; 4.2% vs 16.4%, p  = 0.006), while patient preference was the leading cause to choose a LP in the younger (47.2% vs 5.6%, p < 0.001). Median overall procedural (52 [40–70] vs 50 [40–65] mins) and fluoroscopy time were similar in both groups. 4.3% of patients experienced periprocedural complications, without differences among groups. Threshold values were higher in the younger, both at discharge and at last follow-up (0.63 [0.5–0.9] vs 0.5 [0.38–0-7] V, p  = 0.004). Conclusion: When considering LP indications, patient preference was more common in younger, while infective and vascular concerns were more frequent in the older cohort. Rates of device-related complications did not differ significantly. Younger patients tended to have a slightly higher pacing threshold at mid-term follow-up. Highlights: In a large multicenter, real-world leadless-pacer (LP) registry, young and middle-aged adults (≤50 years old) represented the 6.2% of the entire cohort. The main reason for choosing an LP in patients ≤50 years old was patient preference, while infective and vascular concerns, as well as operator choice, were the most common for older patients (>50 years old). No significant difference in periprocedural characteristics or complications were observed between the two groups Few device-related reinterventions were detected over a mid-term follow-up, with no differences between the two cohorts.